2014
DOI: 10.1371/journal.pone.0094296
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Cytokine Production In Vitro Induced by Ancient and Modern Beijing Mycobacterium tuberculosis Strains

Abstract: It is unclear to what extent the host-responses elicited by Beijing versus non-Beijing strains of Mycobacterium tuberculosis (MTB) contribute to the predominance of modern Beijing strains in Taiwan and some other Asian countries. The purpose of this study was to compare the expression profiles of virulence-related genes in human monocyte-derived macrophages infected in vitro with Beijing (ancient and modern strains) and non-Beijing strains (EAI strains) of MTB that are epidemic in Taiwan. We found that modern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 30 publications
(40 reference statements)
1
30
1
1
Order By: Relevance
“…For example, a recent study showed "modern" Beijing caused more histopathological changes and mortality in mice (56). Most of all, three more recent studies all found that "modern" Beijing strains induced lower and/or delayed proinflammatory that may enable the bacteria to escape from host immune response (57)(58)(59). Epidemiologically, numerous studies from various geographical settings have suggested a higher transmissibility of "modern" Beijing genotype, as indicated by increased prevalence in young people (i.e., a proxy for ongoing transmission) (12,23,51,60), or a higher genotypic clustering proportion than "ancient" genotype (26,52,55).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study showed "modern" Beijing caused more histopathological changes and mortality in mice (56). Most of all, three more recent studies all found that "modern" Beijing strains induced lower and/or delayed proinflammatory that may enable the bacteria to escape from host immune response (57)(58)(59). Epidemiologically, numerous studies from various geographical settings have suggested a higher transmissibility of "modern" Beijing genotype, as indicated by increased prevalence in young people (i.e., a proxy for ongoing transmission) (12,23,51,60), or a higher genotypic clustering proportion than "ancient" genotype (26,52,55).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments in animals, particularly in rabbits and mice, have shown that these strains are highly virulent, with increased dissemination and earlier death of the infected animals (Manca et al, 2001;Tsenova et al, 2005 that the host response against modern and ancestral MTB lineages is different (Chakraborty et al, 2013). Specifically, a more rapid disease progression and a more elevated transmission potential have been observed following infection by modern lineages (Portevin et al, 2011;Reiling et al, 2013;Chen et al, 2014). Based on these epidemiological and experimental data, it seems clear that MTB has evolved towards an increased transmission and virulence potential.…”
Section: Mtb and The Mtbc: A History Of Hostsmentioning
confidence: 99%
“…Disease caused by modern Beijing MTB strains conferred a risk of TB recurrence, despite having less frequent drug resistance than that caused by the ancient Beijing genotype. Previous reports indicate that modern Beijing strains produce lower levels of proinflammatory cytokines [37,38] and have a higher survival in macrophages [38] than ancient Beijing strains. These factors may facilitate persistent infection or reactivation from latent infection, although investigation of these properties at sublineage levels has only just begun.…”
Section: Discussionmentioning
confidence: 94%